Feasibility of intercropping medicinal plants in black pepper garden - V K Raju, S Hamza, K S Krishnamurthy, C K Thankamani, K Kandiannan, M S Madan, (Journal of Spices and Aromatic Crops, 2012)
The feasibility of cultivating medicinal plants in black pepper (Piper nigram L.) plantation was studied at Ambalavayal (Kerala). The plants tested were Adhatoda beddomei, Desmodium gangeticum, Pseudarthria viscida, Ayapana triplinervis, Pogostemon cablin and Plumbago rosea in a fifteen year old black pepper plantation. The results indicated that black pepper yield (2100 kg ha-1) was higher under intercropping situation compared to sole crop (1675 kg ha-1). Among the medicinal plants, maximum black pepper equivalent yield (PEY) (2100 kg ha-1) was recorded in P. rosea followed by P. cablin (2000 kg ha-1). Maximum net return was obtained from black pepper + P. rosea followed by P. cablin. The benefit: cost ratio was highest for inter cropping P. rosea (3.5) followed by P. cablin (3.3) and A. triplinervis (3.3).